Understanding the hydrocarbon prospect of Buzdar block, Southern Indus basin, Pakistan, by using 2-D seismic data: A case study - HUSSAIN, Hamid; SHUANGXI, Zhang; ABID, Muhammad (Contributions to Geophysics and Geodesy, 2019)
The sub-surface structural analysis to understand the geology and tectonics of an area is always useful to locate the hydrocarbon resources. Oil and gas based energy supplies have become a vital source for Pakistan, which is passing through an era of severe energy crisis. The study area, Buzdar block, in the southern Indus Basin is tectonically an extensional regime and is expected to have a huge hydrocarbon potential. In this study, we did the interpretation of the migrated seismic lines of the 872-SGR-527, 872-SGR-529, 872-SGR-531, 872-SGR-532 of Buzdar block, District TandoAllahyar, Sindh. The lines 872-SGR-529, 872-SGR-531, 872-SGR-532 were oriented W–E whereas the line 872-SGR-527 was oriented NW–SE. The obtained data was analysed and three reflectors were marked named top Khadro Formation, top lower Goru formation and top Chiltan limestone (probable). Through this study faults have been also marked on seismic lines which are normal faults by nature; collectively form horsts and grabens which is the evidence of effect of extensional tectonics in the area. Time contour maps were also generated. After that, time was converted into depth with the help of well velocity from VSP data for lower Goru formation and average velocity for Chiltan limestone (probable) from regression analysis. Finally, depth contour maps were generated which helped to know the basic mechanism of tectonic movement in the area. On the basis of present analysis we propose that a well may be drilled at Lower Goru formation near fault F1 on western side at a depth of 1370 meters and at 1290 meters near fault F4 on eastern side.